1999
DOI: 10.2144/99261st02
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of PCRs by Partial Restriction Digestion of Genomic Templates

Abstract: Genomic DNA preparations derived from mammalian cells can often exhibit poor template activity in PCR, particularly when carried out on target sequences present at low copy number. Using genomic DNA bearing SV40 sequences integrated into host chromosomal DNA at low copy number as a target, we show that template efficiency can be dramatically enhanced after treatment of the genomic template with restriction enzymes for varying periods of time. Also, our results indicate that, while template activity was enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Prior to actual analysis, we first evaluated template amplification in digital panels by comparing results with undigested genomic DNA and genomic DNA digested with either Taq I or Msp I restriction endonuclease. Enhancement of amplification efficiency has been observed previously following fragmentation of target genomic DNA with restriction enzymes . The results confirm that digestion of lambda genomic DNA with either Taq I or Msp I improves efficiency of target amplification and reduces the proportion of positive partitions with a Ct >30 compared to undigested DNA.…”
Section: Resultssupporting
confidence: 85%
“…Prior to actual analysis, we first evaluated template amplification in digital panels by comparing results with undigested genomic DNA and genomic DNA digested with either Taq I or Msp I restriction endonuclease. Enhancement of amplification efficiency has been observed previously following fragmentation of target genomic DNA with restriction enzymes . The results confirm that digestion of lambda genomic DNA with either Taq I or Msp I improves efficiency of target amplification and reduces the proportion of positive partitions with a Ct >30 compared to undigested DNA.…”
Section: Resultssupporting
confidence: 85%
“…An investigation of the impact of circular versus linear DNA template was also performed using microfluidic dPCR (Figure ). It has previously been demonstrated that the type of template can affect quantification values when using qPCR. , DNA fragmentation or plasmid linearization can increase amplification efficiency and minimize bias in estimation of the true copy number. , In the experiment described here, directly comparable aliquots of ADH template were evaluated in both circular and linearized forms. The same eluate was either digested ( n = 3 reactions) or undigested ( n = 3 negative control digest reactions) prior to dilution to ∼57 copies/panel, based on Nanodrop UV spectrophotometry estimations.…”
Section: Resultsmentioning
confidence: 99%
“…Dilutions into a ddPCR reaction that are less than 20-fold would require a genome concentration in the lysed AAV sample that is even lower than 80 fM to get 2,500 copies/μL. Note that the pAV-CMV-GFP data uses HindIII, which has a single cleavage site in pAV-CMV-GFP that is located outside of all the milepost assays, instead of a no enzyme condition, to convert the plasmid to a linear conformation and minimize any potential quantification bias resulting from amplicon access in supercoiled plasmids [ 9 , 25 , 26 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%